Structural, magnetic and catalytic properties of La2-xBaxCuO4 (0 ≤ x ≤ 0.5) perovskite nanoparticles. Issue 15 (15th October 2018) - Sukumar, M.; Kennedy, L. John; Vijaya, J. Judith; Al-Najar, B.; Bououdina, M.
Abstract: Barium doped La2 CuO4 perovskite nanoparticles were synthesized via microwave assisted combustion method. The effects of Ba 2+ doping on structural, optical, magnetic and catalytic activity of La2 CuO4 have been studied by X-ray diffraction (XRD), Fourier transform infrared spectroscopy (FTIR), diffuse reflectance spectroscopy (DRS), scanning electron microscopy (SEM) and energy dispersive X-ray analysis (EDX) and vibrating sample magnetometer (VSM) techniques. The XRD patterns of pure La2 CuO4 and La1.9 Ba0.1 CuO4 confirmed the formation of perovskite structure without impurities. However, with increasing Ba 2+ content in the range 0.2–0.5, phase transformation from orthorhombic to tetragonal structure, occurred. The average crystallite size of orthorhombic and tetragonal phases were in the range 45.2–52.2 nm and 0.5–41 nm, respectively. The appearance of FT-IR bands at around 685 and 517 cm −1 were correlated to the La-O and Cu-O stretching modes of orthorhombic La2 CuO4 phase. The direct band gap estimated using Kubelka–Munk (K–M) method decreased with the increase in Ba 2+ content (1.88–1.64 eV), due to the formation of sub-bands in the energy band gap. Magnetic measurements of doped La2 CuO4 samples showed either para- or ferro-/para- magnetic behaviour at room temperature. The catalytic activity (oxidation) tests carried out in a batch reactor operating under atmospheric conditions indicated that the prepared catalysts, in particular (La1.7 Ba0.3 CuO4 ), showed excellent catalytic activity.